Therapeutic option for children with esophageal caustic stenosis - Ortolan, Erika Veruska Paiva [UNESP]; Bustamante, Thais França; Takegawa, Bonifácio Katsunori [UNESP]; Mendonça, Fernanda Alves; Rodrigues, Antonio Marcos; Mendes, Élson Felix (Wiley, 2008)
Caustic ingestion is a leading cause of esophageal stenosis in children. Herein we report four cases using mitomycin C (MMC), a drug that inhibits cell division, protein synthesis and fibroblast proliferation and has been used as an adjuvant therapy for caustic esophageal stenosis that is recalcitrant to conventional dilation techniques. A retrospective chart review was performed on four pediatric patients with severe, recurrent esophageal stricture after caustic ingestion. The patients had required six to 20 esophageal dilations over a 4-16-month period before MMC application. MMC was applied after an endoscopic dilation on saturated pledgets at a dose of 0.1 mg/mL for 2 min in the area where the strictures had been lyzed. From the four children treated with MMC, two have been asymptomatic for 16 and 20 months and two still require esophageal dilation, however, at longer intervals. All patients have shown satisfactory weight gain with food intake exclusively per oral. Although further studies are required, there is strong evidence that MMC is a safe and effective adjuvant therapy in the treatment of esophageal caustic stenosis. © 2008 The Authors.
Keywords: Caustic stenosis; Esophageal stenosis; Mitomycin C; mitomycin C; adjuvant therapy; case report; child; esophagitis; esophagoscopy; esophagus stenosis; esophagus surgery; female; human; male; medical record review; surgical technique; treatment outcome; treatment response